2003
DOI: 10.1128/jcm.41.4.1507-1511.2003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Methods for Detection of Chlamydia trachomatis and Neisseria gonorrhoeae Using Commercially Available Nucleic Acid Amplification Tests and a Liquid Pap Smear Medium

Abstract: Annual screening for Chlamydia trachomatis infection is currently recommended for sexually active women 15 to 25 years old and for women older than 25 if they have a new or multiple sex partners and have not used condoms during the previous 3 months. Annual screening for cervical abnormalities using the Pap smear has achieved a substantial reduction in morbidity and mortality from cervical cancer. Screening for Neisseria gonorrhoeae infection has likely contributed significantly to the reduction in the rates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
32
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 12 publications
2
32
0
Order By: Relevance
“…Hopwood et al (7), testing CS and ThinPrep samples, showed 100% concordance of 19 LCR positives and 562 negatives, which were stable for 5 months. Koumans et al (9) tested ThinPrep samples from 255 sexually active adolescent women, using LCR for C. trachomatis and N. gonorrhoeae, and also performed other forms of testing on urine and CS samples (LCR for C. trachomatis and N. gonorrhoeae, PCR for C. trachomatis and N. gonorrhoeae, transcription-mediated amplification for C. trachomatis, and culture), which broadened the reference standard for comparison of tests and samples to diagnose infected patients. They reported strong agreement (0.97) for C. trachomatis between LCR on ThinPrep and LCR on CS samples collected into the kit transport medium (kappa, 0.92, where kappa is a statistical measurement of interobserver agreement which compensates and corrects for the proportion of agreement that might be due to chance); for N. gonorrhoeae the agreement was 0.99 (kappa, 0.96).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hopwood et al (7), testing CS and ThinPrep samples, showed 100% concordance of 19 LCR positives and 562 negatives, which were stable for 5 months. Koumans et al (9) tested ThinPrep samples from 255 sexually active adolescent women, using LCR for C. trachomatis and N. gonorrhoeae, and also performed other forms of testing on urine and CS samples (LCR for C. trachomatis and N. gonorrhoeae, PCR for C. trachomatis and N. gonorrhoeae, transcription-mediated amplification for C. trachomatis, and culture), which broadened the reference standard for comparison of tests and samples to diagnose infected patients. They reported strong agreement (0.97) for C. trachomatis between LCR on ThinPrep and LCR on CS samples collected into the kit transport medium (kappa, 0.92, where kappa is a statistical measurement of interobserver agreement which compensates and corrects for the proportion of agreement that might be due to chance); for N. gonorrhoeae the agreement was 0.99 (kappa, 0.96).…”
Section: Discussionmentioning
confidence: 99%
“…There are three liquidbased Pap tests (LPTs) approved by the United States Food and Drug Administration (FDA): PreservCyt ThinPrep (Cytyc, Boxborough, MA), SurePath (TriPath Care Technologies, Burlington, NC), and Cytotek MonoPrep (Monogen, Inc., Vernon Hills, IL). Liquid-based cytology has provided greater Pap testing accuracy, and the sample may serve as a specimen to test for infectious agents, such as human papillomavirus (2,11), Chlamydia trachomatis (5,14), and Neisseria gonorrhoeae (6,9). The APTIMA COMBO 2 assay, APTIMA CT assay for Chlamydia trachomatis, and AP-TIMA GC assay for Neisseria gonorrhoeae are transcriptionmediated amplification tests that utilize target capture specimen processing for the in vitro qualitative detection of rRNA from C. trachomatis and/or N. gonorrhoeae.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of the BioStar Chlamydia OIA was previously evaluated for the detection of C. trachomatis in neonatal conjunctivitis (8) and in urogenital infections of women attending sexually transmitted disease (STD) clinics (6,12). In this study, we evaluated, for the first time, the performance of the BioStar Chlamydia OIA in an inner city adolescent female population (5). Two hundred sixty-one female adolescent patients, 13 to 19 years old, who were enrolled in a larger longitudinal study at a public pediatric clinic in Atlanta, GA, were included in our sample (5).…”
mentioning
confidence: 99%
“…Endocervical swab specimens for the BioStar Chlamydia OIA, culture, enzyme immunoassay, and the NAATs were collected by clinicians during the pelvic examination. The BioStar Chlamydia OIA (BioStar, Inc., Boulder, CO) and all of the other diagnostic tests were performed according to the manufacturer's protocol and specifications (5).…”
mentioning
confidence: 99%